Controllably Engineering Mesoporous Surface and Dimensionality of SnO2 toward High‐Performance CO2 Electroreduction. (2nd August 2020) - Wei, Facai; Wang, Tingting; Jiang, Xiaolin; Ai, Yan; Cui, Anyang; Cui, Jing; Fu, Jianwei; Cheng, Jiangong; Lei, Lecheng; Hou, Yang; Liu, Shaohua
Abstract: Currently, the precise control of the architecture and surface of functional materials for high‐performance still remains a great challenge. Here, a feasible approach is presented to synchronously manipulate mesoporous surface and dimensionality of SnO2 catalysts into hierarchically mesoporous nanosheets and nanospheres within one simple reaction system. By adjustment of the hydrophobic chain length of different fluorinated surfactants, 0D SnO2 nanospheres with average size of 165 nm, and 2D SnO2 ulthrathin nanosheets with thickness of 22.5 nm with the distinct dimensionalities are separately obtained (one stone, two birds), both of which are well decorated with ordered mesopore arrays on their surfaces (pore size of 16 nm). The following calcination gave rise to the formation of hierarchically mesopores (5 and 16 nm, respectively) with high crystallization and improved surface area (96.8 m 2 g −1 ). The resultant mesoporous SnO2 nanosheets as catalyst for CO2 electroreduction reaction (CO2 RR) exhibit excellent selectivity, with a high Faraday efficiency (FE) of HCOOH reaching up to 90.0% at −1.3 V and C 1 FE of 97.4% at −1.2 V versus reversible hydrogen electrode, as well as long‐term stability, which is among the best performance compared to reported SnO2 materials, thanks to the collective contributions of the unique architecture and mesoporous structure. Abstract : The synchronous control of mesoporous surfaces and dimensionality/architecture of materials within one simple system is achieved via a facile self‐assembly method, the resultant ultrathin mesoporous SnO2 nanosheets exhibits excellent Faraday efficiency of 90.0% at −1.3 V ( C 1 > 97.4% at −1.2 V) and good stability, superior to most of the reported SnO2 materials toward CO2 electroreduction.